Pengembangan Lembar Kerja Siswa Tematik Tema Indahnya Persahabatan Berbasis Inkuiri Terbimbing di Kelas III SDN Polisi 4 - Candraini, Hesti; Hayu, Wiworo Retnadi Rias; Kurniawati, Atin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to develop and test the feasibility of Thematic Student Worksheets (LKS) based on Guided Inquiry as a handbook or self-learning material for third-grade students on the theme of Beautiful Friendship, with the sub-theme of Plant Friends in the 2013 Curriculum. The main material of the LKS includes friendship towards all living beings. This research is a type of R&D research adopting the 4D model development steps, but in this study, only 3D was used, namely: Define, Design, and Develop. The research instrument used is a product validation questionnaire conducted by one expert, one material expert, and three elementary school teachers. Product trials were conducted on third-grade students at SDN Polisi 4 Bogor, with 6 students as individual trial subjects and 28 students as limited trial subjects. Data analysis used quantitative and qualitative methods using a Likert scale. The result of this research is the "Plant Friends" LKS based on Guided Inquiry in third grade at SDN Polisi 4 Bogor, which is of very good quality based on assessments from material experts, media experts, teacher assessments, individual assessments, and limited trial assessments. Based on this data analysis, the Thematic LKS "Plant Friends" based on Guided Inquiry developed falls into the category of very good, making it suitable for use as self-learning material for third-grade students in elementary school.